EVALUATION OF LEBONG DISTRICT REGIONAL REGULATION NUMBER 12 OF 2011 CONCERNING TERMINAL LEVIES - Febi Irawan Irawan; Bobby Mandala Putra; Edi Darmawi (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
This research aims to evaluate Lebong Regency Regional Regulation Number 12 of 2011 concerning Terminal Retributions. The research results show that the implementation of Lebong Regency Regional Regulation Number 12 of 2011 concerning terminal fees has not run optimally. This can be seen from the lack of human resources and low competence in the field of transportation and terminals, lack of functioning of terminals, inadequate facilities and infrastructure, inadequate socialization of regional regulations, lack of firm control and enforcement carried out by the Transportation Service and UPT terminals to restore terminal functions are equipped with adequate facilities, and collaborate with the police in carrying out control and taking action against violations that occur.